2017
DOI: 10.3390/rs9070698
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Wind Farm Impacts on Local Vegetation Growth in Texas and Illinois Using MODIS Vegetation Greenness Measurements

Abstract: This study examines the possible impacts of real-world wind farms (WFs) on vegetation growth using two vegetation indices (VIs), the Normalized Difference Vegetation Index (NDVI) and Enhanced Vegetation Index (EVI), at a~250 m resolution from the MODerate resolution Imaging Spectroradimeter (MODIS) for the period 2003-2014. We focus on two well-studied large WF regions, one in western Texas and the other in northern Illinois. These two regions differ distinctively in terms of land cover, topography, and backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…However, about 40% of our wind farm samples did not decrease vegetation and instead showed a higher peak NDVI. These results supported the possibility of non-detectable (Xia and Zhou 2017) or positive vegetation effects (Xu et al 2019) reported in other studies at an individual wind farm. Although the construction and operation of wind farms posed a negative impact on vegetation for most wind farms, such effects could be mitigated by other local factors.…”
Section: Wind Farm Impacts On Local Vegetationsupporting
confidence: 91%
See 1 more Smart Citation
“…However, about 40% of our wind farm samples did not decrease vegetation and instead showed a higher peak NDVI. These results supported the possibility of non-detectable (Xia and Zhou 2017) or positive vegetation effects (Xu et al 2019) reported in other studies at an individual wind farm. Although the construction and operation of wind farms posed a negative impact on vegetation for most wind farms, such effects could be mitigated by other local factors.…”
Section: Wind Farm Impacts On Local Vegetationsupporting
confidence: 91%
“…The upwind and downwind regions of wind farms could cause different impacts (Meyers and Meneveau 2012), but we did not distinguish them in our analyses. There is evidence for undetectable impacts of wind farms on vegetation growth in west-central Texas (Xia and Zhou 2017). Hence, the impacts of wind farms on local vegetation are complex and variable, which are influenced by human activity, altered local climate, or any other undiscovered local factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although in situ data monitoring has the advantages of high data accuracy and distinctive features, it is limited in scale and has a major disadvantage, especially in assessing the ecological and climatic impacts of onshore wind farms in a large-scale context. In situ data monitoring can provide reliable information for the inversion of remotely sensed data, such as inversely assessing near-surface temperatures at different times (Walsh-Thomas et al, 2012; Zhou et al, 2012; Zhou et al, 2013; Harris et al, 2014; Slawsky et al, 2015; Chang et al, 2016; Liu et al, 2021b; Luo et al, 2021; Liu et al, 2022a; Ma et al, 2022; Qin et al, 2022), vegetation indexes (Li et al, 2016; Tang et al, 2017; Xia and Zhou, 2017; Wu et al, 2019; Liu et al, 2022b; Aksoy et al, 2023), landscape patterns (Zhang et al, 2016; Diffendorfer et al, 2019; Guo et al, 2020) and other indicators in order to assess the impacts of onshore wind farms on the localized eco-climate.…”
Section: Methodsmentioning
confidence: 99%
“…Since the measurement of vegetation growth indicators is based on the inversion of satellite remote sensing data, the accuracy of remote sensing data affects the reliability of the final conclusions. An analysis of NDVI and EVI of onshore wind farms in the USA revealed that the variations of both values are within the uncertainty of MODIS data, so the impact of onshore wind farms on vegetation may be related to the uncertainty and noise in the remote sensing data (Xia and Zhou, 2017).…”
Section: Impacts Of Onshore Wind Farms On Localized Ecologymentioning
confidence: 99%
“…2017). Recent studies brought into attention the impact of wind turbines on vegetation on the basis of satellite data analysis (Li et al 2016;Tang et al 2017;Xia and Zhou 2017) or simulations that were conducted for understanding the interplay between wind and vegetation under various scenarios of development (Peringer et al 2016;Fang et al 2018). Even more recently, the influence of wind 4 farms on vegetation structure at local scale was analysed by performing systematic field surveys.…”
Section: Introductionmentioning
confidence: 99%